2011
DOI: 10.1007/s13157-010-0123-x
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrological Functions of a Boreal Wetland

Abstract: Wetlands are important to boreal catchment hydrology and water chemistry regimes because they are often situated at the outlet of headwater basins. There is understanding of runoff and geochemical processes that predominate in these wetlands. However, an investigation to improve understanding of the dynamic of hydrological function is absent. This paper addresses the nature of the collection, storage, transmitting and contributing functions of one typical wetland in Canada's Precambrian Shield. The majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 36 publications
2
32
0
1
Order By: Relevance
“…Canopy resistance was calculated using the Jarvis approach (Spence et al, ; Verseghy, McFarlane, & Lazare, ): rc=rs()LAI()boldFboldsF1F2F3F4 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canopy resistance was calculated using the Jarvis approach (Spence et al, ; Verseghy, McFarlane, & Lazare, ): rc=rs()LAI()boldFboldsF1F2F3F4 …”
Section: Methodsmentioning
confidence: 99%
“…Fen hydrological function was assessed using the Spence () method, with modification, at a daily time step. This method has been employed elsewhere to assess when wetlands are predominantly storing, transmitting, and contributing (Goodbrand et al, ; Spence et al, ). The storage function predominated when the fen outflow rate was lower than the absolute value of daily ΔS.…”
Section: Methodsmentioning
confidence: 99%
“…Morrice et al (2008) found that a similar classification system using flow path as a hydrologic factor did not define hydrologically distinct groups of Great Lakes coastal wetlands. These classification systems based on flowpath did not produce distinct groups in some regions likely because groundwater flow paths can vary, or even reverse, over time within the same wetland (Siegel and Glaser 1987;Siegel et al 1995;Spence et al 2011). Although shallow flow paths in peatlands can be assigned using the presence or absence of inlet and outlet streams, these relatively small streams may have little effect on the overall hydrodynamics in a peatland (Spence et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The HGM class Organic Soil Flat, for example, is described as bogs with predominantly vertical hydrodynamics, whereas the broad class Slope wetlands includes fens defined as having horizontal hydrodynamics (Smith et al 1995). However, peatlands frequently comprise a mosaic of bogs and fens exhibiting complex interacting hydrodynamics along both horizontal and vertical flow vectors (Ingram 1983;Siegel and Glaser 1987;Siegel et al 1995;Reeve et al 2001;Glaser et al 2004;Spence et al 2011). As a compromise, (Hall et al 2002) hybridized the two classes into a Slope/Flat type while developing the guidebook.…”
Section: Introductionmentioning
confidence: 99%
“…The hydraulic connectivity between wetlands also significantly influences runoff generation processes, especially in low relief areas such as the Boreal Plain of Canada (Devito et al, ). Spence et al () further stressed that the position of a wetland within a watershed influences its hydrological functions and that regional hydrological models of the boreal region should include an assessment of the position of wetlands within the hydrographic network (i.e., headwater vs. lower reaches). Overall, such studies reveal that climatic conditions and the intrinsic characteristics of peatlands and their position within the hydrogeological environment can influence runoff generation processes.…”
Section: Introductionmentioning
confidence: 99%